Terra, água e trabalho: impactos sociais e ambientais da eucaliptocultura no Maranhão (1990-2018) - Vilanova, Francisco Rairan dos Santos (2023)
This research analyzes the advancement of eucalyptus monoculture in Maranhão, between the years 1990 and 2018, from the point of view of Environmental History and aspects of Social History. The advance of Brazilian agribusiness in the Cerrado biome gave rise to the agricultural border project that brings together the territories of the states of Bahia, Tocantins, Piauí and Maranhão, which goes by the acronym of MATOPIBA. This project, especially in the case of Maranhão, served as a mechanism to attract businesspeople linked to the timber and grain agro-export sector, who found favorable conditions in the region for land acquisition, tax incentives, financing and water wealth. Added to these factors are legal weaknesses from the point of view of protecting rural populations, the Cerrado that covers a large part of Maranhão's territory. In this sense, we seek to discuss the extent to which the exploitation of eucalyptus, a plant whose morphology depends on a very intense water load, represents a risk to nature, to rural populations and mainly to the Cerrado biome. To this end, we raise a debate that problematizes the tools and mechanisms of the capitalist production model, and, especially, the stance of agribusiness, which consists of a severe transformation of natural resources into raw materials and goods, in a brutal process that minimizes and rejects the rights of vulnerable groups who depend on nature to survive. The time frame ranges from the moment the CELMAR project was implemented in Maranhão, in the early 1990s, until one of the last records of land conflicts involving the eucalyptus monoculture business and local peasants, in the state, in 2018. For this is based on discussions about conflicts over water, a growing phenomenon as large companies restrict access to water sources so that their productive interests are assured. Another important vector is the notion that monocultures must always prevail over heterogeneous agriculture in terms of productive advantages. In this sense, it is necessary to understand the transformation of nature into merchandise in the context of globalization. The sources mainly consist of notebooks on conflicts in the field of the Comissão Pastoral da Terra – CPT, newspaper sources, interviews, production reports, statistical data and leaflets from associations. The methodology comprises data analysis and oral history in association with the bibliography consulted.